Transcatheter aortic valve replacement during the COVID‐19 pandemic—A Dutch single‐center analysis. Issue 1 (21st October 2020) - Rooijakkers, Maxim J.P.; Li, Wilson W.L.; Wollersheim, Laurens W.L.M.; Geuzebroek, Guillaume S.C.; Gehlmann, Helmut; van Garsse, Leen A.F.M.; van Wely, Marleen H.; Verkroost, Michel W.A.; Morshuis, Wim J.; Wertheim, Heiman; van Royen, Niels
Abstract: Background and Aim of the Study: The coronavirus disease 2019 (COVID‐19) pandemic has put an enormous strain on healthcare systems and intensive care unit (ICU) capacity, leading to suspension of most elective procedures, including transcatheter aortic valve replacement (TAVR). However, deferment of TAVR is associated with significant wait‐time mortality in patients with severe aortic valve stenosis. Conversely, there is currently no data available regarding the safety and feasibility of a continued TAVR program during this unprecedented crisis. The aim of this study is to evaluate the safety and feasibility of patients undergoing TAVR during the COVID‐19 pandemic in our center, with specific emphasis on COVID‐19 related outcomes. Methods: All patients who underwent TAVR in our center between February 27, 2020, and June 30, 2020, were evaluated. Clinical outcomes were described in terms of Valve Academic Research Consortium 2 definitions. Patient follow‐up was done by chart review and telephone survey. Results: A total of 71 patients have undergone TAVR during the study period. Median age was 80 years, 63% were men, and 25% were inpatients. Procedural success was 99%. After TAVR, 30% involved admission to the ICU, and 94% were ultimately discharged to the cardiac care unit on the same day. Two patients (3%) had confirmed COVID‐19 a few days after TAVR, and both died of COVID‐19 pneumonia within 2 weeks after hospital discharge. Conclusions: A continued TAVR program during the COVID‐19 pandemic is feasible despite limited hospital resources. However, COVID‐19 related mortality after TAVR is of concern.